(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Today, a parking system is a requirement of the utmost significance. There must be enough room for everyone’s vehicles since everyone owns one. Even some firms are obligated to provide their own private parking. Depending on the requirements of the location, the parking management structure varies. In metropolitan areas, parking systems have major challenges. Finding a parking spot is a major issue for young people today, and there is also a risk of car theft there as well. As a result, parking management systems enable efficient use of parking resources. By using our Vehicle Management System, we want to find a solution to the issue of trying to find a free parking spot in any parking lot using Machine learning and OpenCV. Typically, people put a lot of time and effort (Fuel) into finding the ideal location. By mapping the driver and the vehicle and confirming both at the entrance or exit of the parking place, we are also enhancing the security and safety of the area. So, our main goal is to go above the limitations of the current parking system and create a productive one that is both environmentally and customer-friendly.